In a blink - Thorpe, Kiki.; Christy, Jana (New York : Random House, 2013)
When four friends are whisked out of their ordinary lives to Never Land, home to fairies and mermaids, Queen Clarion and Tinker Bell have to figure out a way for them to get home.
"Disney."
"A Stepping Stone book."
Keywords: Fairies -- Fiction; Magic -- Fiction